2017
DOI: 10.1016/j.bone.2016.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Compound heterozygous variants in NBAS as a cause of atypical osteogenesis imperfecta

Abstract: Background Osteogenesis imperfecta (OI), the commonest inherited bone fragility disorder, affects 1 in 15,000 live births resulting in frequent fractures and reduced mobility, with significant impact on quality of life. Early diagnosis is important, as therapeutic advances can lead to improved clinical outcome and patient benefit. Report Whole exome sequencing in patients with OI identified, in two patients with a multi-system phenotype, compound heterozygous variants in NBAS (Neuroblastoma amplified sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 34 publications
(49 reference statements)
2
52
0
1
Order By: Relevance
“…One component of the MTC (RINT1) was also identified in our screen for genes required for protein secretion ( Bard et al, 2006 ). Mutations in another component NBAS, are linked to dysregulated collagen secretion in atypical osteogenesis imperfecta ( DDD Study et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…One component of the MTC (RINT1) was also identified in our screen for genes required for protein secretion ( Bard et al, 2006 ). Mutations in another component NBAS, are linked to dysregulated collagen secretion in atypical osteogenesis imperfecta ( DDD Study et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…This mode of action is inextricably linked to the formation of rings of TANGO1 at ERES (Liu et al 2017; Raote et al 2017). NBAS mutations in humans cause multisystem disorders (Segarra et al 2015) that do include defects in bone formation (Balasubramanian et al 2017) and can therefore be linked to impaired procollagen transport.…”
Section: Efficient Assembly Of the Copii Coat As A Prerequisite For Pmentioning
confidence: 99%
“…NBAS‐associated facial phenotype and genotype–phenotype correlations. (a–d) Composite photos obtained from patients (Balasubramanian et al, ; Capo‐Chichi et al, ; Kortum et al, ; Maksimova et al, ; Megarbane et al, ; Regateiro et al, ; Staufner et al, ) and age‐/gender‐matched controls. Facial features of subjects with biallelic inactivating/hypomorphic NBAS variants include hypotelorism, thin upper lip, pointed chin, and a progeroid appearance.…”
Section: Introductionmentioning
confidence: 99%
“…So far, 47 different pathogenic NBAS variants have been reported in 71 individuals. To explore possible genotype–phenotype correlations, the available clinical data were collected (Table S5; Balasubramanian et al, ; Capo‐Chichi et al, ; Kortum et al, ; Maksimova et al, ; Megarbane et al, ; Regateiro et al, ; Segarra et al, ; Staufner et al, ; E‐P03.292008: European Society of Human Genetics 2018 meeting). A total of 36 patients have been reported to carry the homozygous p.Arg1914His change associated with the SOPH phenotype (Maksimova et al, ; Park & Lee, ), while two patients were reported to have a skeletal phenotype associated with the homozygous c.6237−3C>G splice‐site change (Palagano et al, ; Prontera et al, ).…”
Section: Introductionmentioning
confidence: 99%